2005
DOI: 10.1016/j.femsle.2004.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between faecal microbial community structure and cholesterol-to-coprostanol conversion in the human gut

Abstract: Intensity of the cholesterol-to-coprostanol conversion in the intestine, as assessed by the coprostanol-to-cholesterol ratio in faeces, was found highly variable among 15 human volunteers, ranging from absent to almost complete cholesterol conversion. The number of coprostanoligenic bacteria in the same faecal samples, as estimated by the most probable number method, was found to be less than 10(6) cellsg-1 of fresh stools in the low-to-inefficient converters and at least 10(8) cellsg-1 of fresh stools in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 31 publications
3
47
0
2
Order By: Relevance
“…Higher amounts of lactic acid bacteria (lactobacilli+bifi dobacteria 10 8 -10 10 cell/g faeces) were observed in case of samples with higher sterol conversion (conversion 85-90%). This fi nding agrees with the data in literature that the level of cholesterol reducing bacteria must be at least 10 6 cell/g of wet stool for effi cient conversion of cholesterol in the human gut, while a population of more than 10 8 cell/g of wet stool leads to nearly complete conversion (VEIGA et al, 2005). Taking into account that most of isolated bacterial converters belong to Bacteroidetes, whose number was low (on average 10 3 cell/g faeces) in studied faecal samples, these data correlate well.…”
Section: Detection Of Faecal Sterolssupporting
confidence: 92%
“…Higher amounts of lactic acid bacteria (lactobacilli+bifi dobacteria 10 8 -10 10 cell/g faeces) were observed in case of samples with higher sterol conversion (conversion 85-90%). This fi nding agrees with the data in literature that the level of cholesterol reducing bacteria must be at least 10 6 cell/g of wet stool for effi cient conversion of cholesterol in the human gut, while a population of more than 10 8 cell/g of wet stool leads to nearly complete conversion (VEIGA et al, 2005). Taking into account that most of isolated bacterial converters belong to Bacteroidetes, whose number was low (on average 10 3 cell/g faeces) in studied faecal samples, these data correlate well.…”
Section: Detection Of Faecal Sterolssupporting
confidence: 92%
“…In a previous study, we established that the population level of cultivable fecal coprostanoligenic bacteria correlated with the intensity of cholesterol-to-coprostanol conversion in the human gut. Indeed, we found that populations containing less than 10 6 , between 10 6 and 10 8 , and more than 10 8 coprostanoligenic bacteria/g (wet weight) of stool are associated with inefficient, intermediate, and high cholesterol conversion patterns, respectively (38). In the present study, fecal communities belonging to the Bacteroides-Porphyromonas-Prevotella group from 11 humans with different cholesterol conversion patterns were profiled by TTGE of amplified 16S rRNA gene fragments in order to estimate the incidence of Bacteroides sp.…”
Section: Resting-cell Experimentsmentioning
confidence: 84%
“…Standard tests of cholesterol-to-coprostanol reducing activity were carried out in standard brain medium (SBM) (pH 7.2 to 7.4), which was derived from the medium described by Brinkley et al (7) and contained the following components (per liter): 20 g lyophilized calf brain, 10 g Casitone, 10 g yeast extract, 5 g KH 2 PO 4 , and 0.5 g sodium thioglycolate. Where indicated below, activity was also assayed in a basal cholesterol (BC) medium (pH 7.5) derived from the medium described by Ren et al (31) and containing (per liter) 10 g Casitone, 10 g yeast extract, 5 g sodium pyruvate, 0.5 g sodium thioglycolate, 1 g CaCl 2 · 2H 2 O, 0.2 g cholesterol, and 1.0 g lecithin, as well as in brain heart infusion-yeast extract-hemin (BHI-YH) medium (pH 7.4) enriched with cholesterol (38) and containing (per liter) 10 g brain heart infusion (Difco), 10 g yeast extract, 10 ml of a 0.1% hemin solution (Sigma-Aldrich Chimie), 0.5 g L-cysteine (Sigma-Aldrich Chimie), 0.2 g cholesterol, and 1 g lecithin. Agar (14 g/liter) was added to BHI-YH medium when required.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations